Synthesis and broadband dielectric-infrared spectroscopy of La1-xSrxMnO3@BaTiO3 nanocomposite. (December 2021) - Nuzhnyy, Dmitry; Bovtun, Viktor; Savinov, Maxim; Kempa, Martin; Petzelt, Jan; Kaman, Ondřej; Klementová, Mariana; Kuličková, Jarmila; Jirák, Zdeněk
Highlights: All-perovskite core-shell nanoceramics of La1-x Srx MnO3 @ BaTiO3 is designed. Small conductivity is determined by tunnelling and temperature activated processes. Ferroelectric transition in BaTiO3 shells in the same temperature range as in the bulk. Ferroelectricity in the smallest BaTiO3 objects ever observed in ceramics. Effective medium modelling explains the giant low-frequency permittivity values. Abstract: The study deals with design, structural and magnetic characterization, electric and magnetoelectric transport and broad-band dielectric spectroscopy of the all-perovskite core-shell composite nanoceramics of 0–3 connectivity, in which ∼50 nm cores of ferromagnetic La0.65 Sr0.35 MnO3 (LSMO) metal are embedded in ferroelectric BaTiO3 (BTO) shells of mean 13 nm thickness. The BTO spacers lead to significant barriers for itinerant carriers, at low temperatures being transmitted by tunnelling, but additional conduction paths are temperature activated by hopping across them. The dielectric, terahertz and infrared spectroscopy data of LSMO@BTO are modelled by effective medium approaches, which enables to explain the broad dielectric and AC conductivity dispersion including the giant low-frequency permittivity values. Temperature dependant terahertz transmission spectroscopy clearly indicates the ferroelectric transition in the nano-BTO shells in the same temperature range as in the bulk BTO. Graphical abstract: Image, graphical abstract